A day off from field work, at Knight's Hill esker, near Churchill on Hudson Bay, Manitoba, Canada. - Bazely, Dawn R. (1981)
Michelle Kortnaar and Susan Cargill, Botany Department, University of Toronto (Robert L. Jefferies' laboratory group) on the esker at Knight's Hill, east of Churchill, Manitoba, Canada. The view is of La Pérouse Bay to the east with Hudson Bay, Manitoba, Canada, on the horizon.